Myocardial fibrosis quantification methods by cardiovascular magnetic resonance imaging with contrast-enhancement in patients with Fabry disease. (13th July 2021) - Sokolska, J; Karolyi, M; Bataiosu, D; Gastl, M; Weber, L; Sokolski, M; Gruner, C; Manka, R
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): National Agency for Academic Exchange (NAWA). Background. Presence and extent of late gadolinium enhancement (LGE) in patients with Fabry disease (FD) is a predictor of adverse cardiac events. However there is no gold standard method to quantify the amount of myocardial fibrosis in cardiac magnetic resonance imaging (CMR). Purpose. The aim of this study was to establish the most reliable and reproducible technique for quantifying LGE in patients with FD. Methods. 68 patients with FD (40% male, 40 ± 16 years old) treated in our outpatient clinic, who underwent CMR with administration of 0.2 mmol of gadobutrol per kilogram of body weight between December 2012 and March 2019 were enrolled into the study. Presence of LGE was described in 25 patients (37%). Twenty patients underwent CMR with the same LGE sequence (Philips 1.5 Tesla, two-dimensional multi-breath-hold inversion recovery sequence) and were enrolled into further analysis. LGE quantifications were performed using gray-scale thresholds with 2, 3, 4, 5 and 6 standard deviations (SD) above the mean signal intensity for the remote myocardial tissue, full width at half maximum method (FWHM), visual assessment with threshold (VAT) and fully manual method (MM; Philips IntelliSpace Portal 10). LGE quantifications were done twice by the same observer in different time periods and once by another observer. Intraclass correlation coefficient (ICC), Bland- Altman analysis and coefficient of variation (CV) were used to assess intra- and interobserver reliability and reproducibility. Results. The mean quantity of fibrosis mass  (in gram) in all studied patients was: 35.5 ± 18.7 at 2SD, 21.0 ± 12.8 at 3SD, 12.7 ± 8.5 at 4SD, 8.0 ± 5.7 at 5SD, 5.3 ± 4.1 at 6SD, 1.9 ± 1.8 at FWHM, 8.6 ± 7.4 at VAT and 9.1 ± 6.1 at MM. Intra-observer reliability of almost all studied LGE quantification methods was excellent, with a range of ICCs from 0.90 for 6SD to 0.95 for VAT, with one exception for FWHM, which had good intraobserver reliability (ICC 0.84; all P < 0.05). Interobserver reliability was excellent for VAT (ICC 0.94) and good for all other LGE quantifications methods (range of ICCs from 0.76 for MM to 0.87 for 5SD, all P < 0.05). 5SD had the lowest CV (6%) for intraobserver reproducibility and 2SD and VAT for interobserver reproducibility (35% and 38%). FWHM had the highest CV for both intra- and interobserver reproducibility (63% and 94%, accordingly). Conclusions: 1. All studied methods of LGE quantification in patients with FD and presence of myocardial fibrosis have good to excellent intra- and interobserver reliability. 2. The total amount of LGE differs in studied LGE quantifications methods. Therefore in clinical practice it is important to report which technique of LGE quantification was used and choose the same for CMR-follow up. 3. FWHM might be avoided for LGE quantification in patients with FD due to the highest intra- and interobserver variability in comparison to other available techniques.